Geomorphological and sedimentological evidence of Late Pleistocene glaciation in the Babia Góra massif (Western Flysch Carpathians, Poland) - Kłapyta, Piotr; Siemek, Dawid (Quaestiones Geographicae, 2025)
The legacy of Pleistocene glaciation in the Babia Góra massif (1725 m a.s.l.) has been the subject of vigorous debate for over a century. These controversies have been largely influenced by the poor preservation of glacial landforms and their extensive overprint by rock slope failures (RSFs). In this context, geomorphological criteria alone have proven insufficient for a comprehensive interpretation of glacial features in flysch lithology, which has been heavily shaped by landslides. In this study, we present the results of field and LiDAR-supported geomorphological mapping, clast morphology analysis and micromorphological examination of sand-sized quartz grains. This multiproxy approach, when combined with previously published Schmidt-hammer data, provides robust evidence for the presence of glaciation in the Babia Góra massif. The Late Pleistocene palaeoglacier (area 0.87 km2, 2.2 km long) was reconstructed in the headwaters of the Szumiąca Woda valley. Mapped latero-frontal moraines mark the extent of the glacier front at 930 m a.s.l. The glacier equilibrium line altitude (ELA) calculated from glacier hypsometry with the area altitude balance ratio (AABR) 1.6 was 1272 m. However, after accounting for the topographic effect of additional snow accumulation, the climatic ELA was recalculated and placed at 1354 m a.s.l. These findings suggest that, in addition to the previously known eastward horizontal gradient of ELA rise, a southward trend of rising ELA was also observed across the Western Carpathians.